Restenosis Rates in Small-Vessel Disease: Drug-Coated Balloons vs. Drug-Eluting Stents in Diabetic and Non-Diabetic Populations - Aamir Nawaz Khan, Nimra Nabi, Muhammad Saleem, Rameez Akhtar, Muhammad Kashif Iltaf, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aimed to assess the effect of diabetes mellitus on the clinical outcome of patients treated for new lesions with drug-eluting stents (DES) or drug-coated balloons (DCBs). Methods: In this study 260 patients of both genders either with diabetes or not were presented. The specific demographic information of the cases that were enrolled was documented after obtaining written informed consent. 130 patients of group I received drug-coated balloons and group II received drug eluting stunts in 130 cases. Outcomes among both groups were compared with diabetes and non-diabetes cases. Results: The patients mean age was 62.76±14.58 years with BMI 29.52±6.51 kg/m2 in group I and mean age of the cases of group II was 65.16±8.51 years with mean BMI 28.41±8.38 kg/m2. Both groups of non-diabetic subjects did not vary substantially in the rates of major adverse cardiac events (MACE), nonfatal myocardial infarction (MI), or target vessel revascularization (TVR). We found significantly reduction in TVR among patients of DM in group I as compared to group II with p value <0.002. Conclusion: There is no significant difference in the rates of major adverse cardiac events (MACE) following DCBs and DES for de novo coronary lesions in women and men with diabetes. When DCB was used instead of DES, the necessity for TVR in diabetic people was significantly reduced. Keywords: Drug-Coated Balloons, Drug-Eluting Stents, diabetic, MACE, DCB, DES, TVR, non-diabetic